Introduction to Lampung Tapis: a Variety of Beautiful Culture From Indonesia - Achmad Chaedar Yasin Bakhtiar; Ahmad Rafinur; Muhtarom Muhtarom; Devi Saputri; Ayi Saprudin; Rindu Rika Gamayuni (Universitas Palangka Raya, 2025)
Lampung Tapis is a traditional Indonesian fabric that reflects the rich culture of the people of Lampung. Decorated with gold thread embroidery, Tapis symbolises aesthetic values, philosophy and social identity. In the context of globalisation, Tapis faces challenges in maintaining its sustainability due to the lack of appreciation and access to international markets. This research aims to introduce Lampung Tapis to the global community through promotion in international forums. The methods used included visual presentation, cultural narrative, and physical product exhibition at the Problematic Seminar on Global Accounting in Kyoto, Japan. The results of the activity showed an increase in participants' appreciation of the beauty and cultural values of Tapis Lampung, as evidenced by the audience's high interest in this fabric as a cultural symbol and business opportunity. The cultural story-based marketing strategy is an effective approach in introducing Tapis in the global market, while supporting its economic sustainability. In addition, cross-cultural collaboration and the use of digital platforms are seen as important for expanding market networks. By combining tradition and innovation, Lampung Tapis has great potential to become an Indonesian cultural icon at the international level. This research recommends strengthening synergies between the government, local artisans and the private sector to support the promotion and regeneration of Lampung's Tapis industry. This step will not only preserve the cultural heritage but also improve the welfare of the artisan community.